Evolution of the synapse transcriptome - Izquierdo Barraza, Abril (2019)
The vast cognitive repertoire seen within the animal kingdom from rudimentary forms of habituation and information-processing to highly complex cognitive processes that confers the ability to adapt to challenging environments is a topic of great interest. The presynaptic and postsynaptic terminals of the synapse form an immensely structured protein network, the origin of which has been proposed to precede the origin of multicellularity in elementary cell signalling pathways. Such molecules were central for the arrangement of macromolecular complexes through genome duplications and posterior diversification in the vertebrate evolution. Yet, mutations in the postsynaptic density (PSD) are associated to more than 130 neurological alterations. It is therefore fundamental to better understand brain gene expression and evolution of these genes. Proteomic analysis of the synapse have characterised more than 1,500 proteins, however strikingly, there is a lack of research using recent transcriptomics approaches.